Inactivation kinetics of invertase in honey and honey–glucose syrup formulations: effects of temperature and water activity. (6th July 2016) - Sramek, Martin; Woerz, Benjamin; Horn, Helmut; Weiss, Jochen; Kohlus, Reinhard
Abstract: BACKGROUND: The high viscosity and stickiness of honey in its natural state causes handling difficulties, therefore the demand for honey powder is continuously increasing. Powder preparation has to be performed gently because of the thermo‐ and oxidation‐ sensitive nature of honey. The aim of this study was to determine the degradation of invertase during drying as an indirect measure of the retention of valuable honey nutrients. RESULTS: The reaction kinetics were estimated in polyfloral honey and honey–glucose syrup (GS) formulation and the impact of temperature (40–70°C) and water activity ( a w 0.23–0.81) was established. The honey–GS formulation (55:45 w/w) was intended for the preparation of high‐grade honey powders using the vacuum‐drying method. Invertase inactivation at temperatures below 60°C followed first‐order kinetics. At 60°C high dilution ( a w 0.81) and at 70°C, heterogeneous inactivation behaviour was observed. The best fit of invertase heterogeneous inactivation kinetic was achieved with the Cerf two‐fraction model. The GS addition showed a stabilizing effect on invertase during thermal degradation. CONCLUSION: The data on invertase inactivation gathered here can be utilized to select optimal parameters for honey vacuum‐drying and other thermal processes in order to achieve maximum invertase retention. © 2016 Society of Chemical Industry